2012
DOI: 10.2147/ijn.s30060
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and characterization of gold-conjugated polyphenol nanoparticles as a novel delivery system

Abstract: Nanogold particles are commonly used in nanomedicine. We generated physical nanogold (pNG) conjugated with different ratios of epigallocatechin-3-gallate (EGCG) and evaluated its physicochemical properties, antioxidant activity, and cytotoxicity in vitro as well as anticancer activity in vivo. Results showed that the EGCG-pNG conjugates were successfully prepared at ratios between 23:1 and 23:5, with the percentage of EGCG content increasing with the EGCG:pNG ratio from 23:1 (2.0% ± 0.02%) to 23:5 (28% ± 0.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The EGCG-pNG particles at a ratio of 50 μM:1.25 ppm contained 27% EGCG conjugate, were around 64.7 nm in size, and had a zeta potential of −3.36 mV; these particles were used for further study. In our previous report,22 EGCG-pNG at a ratio of 50 μM:2.5 ppm showed longer EGCG activity half-life (110 days versus [vs] 5 hours), longer controlled release time (2 hours vs 30 minutes), and higher antioxidant activity (four times) than EGCG alone. Well nanoparticle dispersion was also deduced with an optimum zeta potential (±30 mV), which is more likely to occur for charged particles due to electrostatic repulsion 23…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The EGCG-pNG particles at a ratio of 50 μM:1.25 ppm contained 27% EGCG conjugate, were around 64.7 nm in size, and had a zeta potential of −3.36 mV; these particles were used for further study. In our previous report,22 EGCG-pNG at a ratio of 50 μM:2.5 ppm showed longer EGCG activity half-life (110 days versus [vs] 5 hours), longer controlled release time (2 hours vs 30 minutes), and higher antioxidant activity (four times) than EGCG alone. Well nanoparticle dispersion was also deduced with an optimum zeta potential (±30 mV), which is more likely to occur for charged particles due to electrostatic repulsion 23…”
Section: Resultsmentioning
confidence: 86%
“…Combined treatment with EGCG and vorinostat or vitamin A has also shown improved and enhanced anti-melanoma efficacy 30,31. In our previous study, EGCG-pNG was also proven to access synergistic anti-cancer ability against bladder cancer 15,22…”
Section: Resultsmentioning
confidence: 95%
“…The authors also demonstrated that the formulation showed preferential toxicity to cancerous cells and an in vivo efficiency in reducing the growth of implanted tumors in mice. The sustained release and the high cytotoxicity to cancerous cells make these nanocarriers promising future nanoformulations to use in cancer therapy [ 52 ]. Recently, EGCG conjugated gold nanoparticles have also been employed for the treatment of cardiovascular diseases.…”
Section: Nanocarriers Used To Deliver Egcgmentioning
confidence: 99%
“…Thus, EGCG-GNPs had 4.91-fold higher cytotoxicity against murine B16F10 melanoma cells compared with EGCG, in vitro [7]. In another in vivo study, EGCG-GNPs had significantly lower MBT-2 tumor volume compared with EGCG when given orally or by intraperitoneal injection in a C3H/He mouse model [65]. However, the magnitude of enhancement of the in vivo anticancer effect of EGCG-GNPs compared with EGCG alone was not as pronounced as that observed in the in vitro studies [29].…”
Section: In Vivo Studiesmentioning
confidence: 91%